(untitled) (International journal of artificial intelligence, 2026)
In the article, during the years of independence, the activities of medical institutions in the Fergana region, the construction, repair and their equipment, the supply of hospitals with modern medical equipment, the importation of dental, physiotherapeutic, X-ray diagnostic devices developed in the countries of the Commonwealth of Independent States, as well as their water, heating and sewage system, telephone communication system, electricity supply, autoclaves, drying cabinets, distiller, modern test-indicators, detergents and disinfectants were analyzed through primary sources.